Perancangan e-Jaminan Mutu Perguruan Tinggi Baru menggunakan metode Waterfall - Nurfitria Ningsi; Yuwanda Purnamasari Pasrun (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
This study is focused on designing e-quality assurance services to improve the performance of the USN Kolaka FTI Quality Assurance group, which during the COVID-19 pandemic was still applying manual SOP submissions and approvals. the importance of designing e-quality assurance considering the magnitude of its support in academic policy making during the new normal adaptation period in order to support the implementation of quality education in accordance with expectations. the results of this study indicate that 95% of users agree that the faculty's e-quality assurance is able to encourage increased work productivity of GJM FTI through the use of the online SOP draft submission feature to approval and automatic review. The importance of adding MONEV and Internal Audit features will maximize the performance of GJM FTI in the future.